Allocation of offshore risk in Malaysia: a call for the application of the Industry Mutual Hold Harmless (IMHH) deed - Wan Zahari, Wan Mohd Zulhafiz (2017)
The contractual allocation of liabilities in the oil and gas projects is becoming an issue of paramount importance since the projects are risky ventures. The allocation of the parties’ respective shares of liability in accidents is typically carried out under standard industry contracts which have been established over many years. However, as a consequence of the private and government litigation arising from the Macondo oil spill in the Gulf of Mexico in 2010 as well as revised perceptions of risk exposure, evidence suggests that operators generally are seeking to modify the established approach to liability allocation through individual contract negotiations with contractors. This scenario has significant and potentially adverse financial implications for the contractors and for the long-term sustainability of the industry. Thus, there is a need to develop a legal mechanism that will achieve a fair distribution of risk between operators and contractors. This research focuses in particular upon the law of Malaysia. It aims at determining the feasibility of implementing the Industry of Mutual Hold Harmless Deed (“IMHH”) in the Malaysian oil and gas industry. Currently, the IMHH applies to the UK’s territory of the North Sea and the Irish Sea. It was created to support and effectively manage the inherent risks in offshore activities in the oil and gas industry whereby a company is considerably in a better position will protect its own people and equipment by providing an indemnification. In this regard, companies are more certain of the risks they must insure and could avoid multiple insurance policies on the same risk. However, it is important to note that some modification of the IMHH model should be made to accommodate peculiar circumstances. The methodology employed in this research will be a comparative analysis which will be carried out in a descriptive, analytic and prescriptive manner.